Upaya Peningkatan Minat Hasil Belajar Siswa Terhadap Pendidikan Agama Katolik Melalui Model Pembelajaran Problem Based Learning Kelas XI SMAN 11 Pekanbaru - Parman Simarmata (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research is entitled: "Efforts to Increase Student Interest in Catholic Religious Education through the Problem Based Learning (PBL) Learning Model for Class XI Students of SMAN 11 PEKANBARU."The aim of this research is to improve student learning outcomes with creative and critical thinking material on church social teachings through the problem based learning (PBL) learning model for class XI students at SMAN 11 PEKANBARU. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation and reflection. Based on the results of action research, the Problem Based Learning (PBL) learning model can improve learning outcomes for creative and critical thinking material on church social teachings for class XI students at SMAN 11 PEKANBARU, Tenayan Raya District, Pekanbaru City. Furthermore, the researcher recommends: (1) Teachers who experience the same difficulties can apply the PBL Learning Model to improve Learning Outcomes for Creative and Critical Thinking Materials on Church Social Teachings for Class XI Students. (2) In order to get maximum results, teachers are expected to better understand the Problem Based Learning (PBL) Learning Model.